2017
DOI: 10.1021/acsami.6b14972
|View full text |Cite
|
Sign up to set email alerts
|

QD-Biopolymer-TSPP Assembly as Efficient BiFRET Sensor for Ratiometric and Visual Detection of Zinc Ion

Abstract: In this work, we report a new type of quantum dot (QD)-based fluorescence resonance energy transfer (FRET) assembly and its utility for sensing Zn in different media. The assembly on the QD scaffold is via first coating of poly(dA) homopolymer/double-stranded DNA, followed by loading of meso-tetra(4-sulfonatophenyl)porphine dihydrochloride (TSPP), both of which are electrostatic, offering the advantages of cost-efficiency and simplicity. More importantly, the biopolymer coating minimizes the interfacial thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…Among the transition-metal ions, zinc is the second most abundant metal, after iron, in the human body. It also plays a vital role in DNA synthesis, neural signal transmission, gene transcription, and apoptosis. Moreover, Zn 2+ disorder usually leads to severe diseases, such as metabolic disorder, Alzheimer disease, cerebral ischemia, infantile diarrhea, and epilepsy. Therefore, to detect the Zn 2+ present in biological and environmental samples, diverse tactics have been proposed, such as electrochemistry, ion selective membrane, inductively coupled plasma mass spectroscopy (ICP-MS), inductively coupled plasma-atomic emission spectrometry (ICP-AES), and atomic absorption spectrometry (AAS). However, these techniques are limited in real applications due to the cost, sample pretreatment requirement, and time consumption. On the contrary, fluorescent probes toward Zn 2+ detection are rather unique due to their low-cost, high sensitivity, and real-time bioimaging applications. Thus, the design of such fluorescent probes is still highly anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Among the transition-metal ions, zinc is the second most abundant metal, after iron, in the human body. It also plays a vital role in DNA synthesis, neural signal transmission, gene transcription, and apoptosis. Moreover, Zn 2+ disorder usually leads to severe diseases, such as metabolic disorder, Alzheimer disease, cerebral ischemia, infantile diarrhea, and epilepsy. Therefore, to detect the Zn 2+ present in biological and environmental samples, diverse tactics have been proposed, such as electrochemistry, ion selective membrane, inductively coupled plasma mass spectroscopy (ICP-MS), inductively coupled plasma-atomic emission spectrometry (ICP-AES), and atomic absorption spectrometry (AAS). However, these techniques are limited in real applications due to the cost, sample pretreatment requirement, and time consumption. On the contrary, fluorescent probes toward Zn 2+ detection are rather unique due to their low-cost, high sensitivity, and real-time bioimaging applications. Thus, the design of such fluorescent probes is still highly anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence resonance energy transfer (FRET) effect was revealed between P3 and P5 . The mixture of P3 and P5 was dissolved in tetrahydrofuran (THF) and then the solution was added dropwise into water with stirring. After THF was evaporated completely, the P3 + P5 NPs were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…170 Motivated by this seminal work, more FRET-based nanostructures based on nanoparticle-dye complexes have been developed for ratiometric sensing and imaging both in vitro and in vivo . Among reported dual-emitting nanoparticle-dye nanoconjugates, core nanomaterials include FRET donors such as QDs, 171176 GQDs, 177 Cdots, 178183 Pdots, 184186 fluorescence MOF, 187 and persistent luminescence nanoparticles (PLNPs), 188 whereas the dyes for FRET acceptors have been traditional organic dyes or fluorescent proteins. 189 Recently, Wu et al reported Cdot-based fluorescent nanoprobes for ratiometric sensing and imaging of intracellular hydrogen peroxide (H 2 O 2 ) based on FRET, where Cdots were used as the FRET donor and the nanocarrier for covalent attachment of a triphenylphosphonium (TPP) ligand for mitochondria targeting and a boronate-protected fluorescein (PFl) for H 2 O 2 recognition (Fig.…”
Section: Ratiometric Fluorescence Nanoprobesmentioning
confidence: 99%